To go or to stay? Examining the relationships between organisational commitment, work ethics, and turnover intention - Mohd Mahudin, Nor Diana; Fauzi, Fatin; Melati, Putifatma Hanum; Janon, Nazariah Shar'ie (John Wiley & Sons, 2016)
Past research has suggested that the rising rate of turnover intention in the banking industry can be attributed, in part, to employees' work ethics and organisational commitment. However, there is limited empirical evidence investigating the role of these two variables, particularly the three components of organisational commitment (i.e., affective, continuance, and normative) play in explaining intention to quit. Responses from 225 full-time bank employees were analysed using hierarchical regression. Results indicate that both global and normative organisational commitment negatively correlated with turnover intention most strongly. Affective and continuance commitment as well as work ethics, however, were not statistically significant predictors of turnover intention. The results suggest that targeting only one component of organisational commitment may not be sufficient to mitigate intention to quit. Hence, fostering similarity between employees' and organisation's values is recommended as this process could build stronger organisational commitment and help lower employees' turnover intention.